COMPARATIVE ANALYSIS OF B2C AND B2B MARKETING STRATEGIES IN CLEANING PRODUCTS INDUSTRIAL ENTERPRISES - Baqoyeva Dilfuza Maqsud qizi (Ecominds Press, 2025)
Companies producing cleaning products stand out in the market not only by product quality but also through their marketing strategies. These companies shape their activities based on customer needs and choose approaches depending on the type of buyer. In B2B marketing, the main focus is on collaboration, service quality, and technical solutions. In contrast, the B2C approach prioritizes emotional connection with the consumer, brand recognition, and convenient pricing policies.